Intelligent responses through network-based answer discovery with advanced reasoning - W, Wong; Basiron, Halizah; Sahib, Shahrin; Goh, Ong Sing (2005)
This paper introduces a network-based answer discovery scheme coupled with some advanced reasoning features that is part of NaLURI (Natural Language Understanding and Reasoning for Intelligence), a knowledge-based question answering system. This move beyond classical logic-based reasoning is necessary in order to provide intelligent responses under suboptimal circumstances or failures and is especially important for question answering systems like NaLURI where the nature of the input varies greatly, causing immense uncertainties during response generation.